Counterfactuals: Does bureaucracy produce unfair workplaces? - Clemens Striebing; Jannick Schneider; Moritz Julian Maier (Australian Journal of Public Administration, 2026)
Abstract Bureaucracy is often used as a metaphor for organisations that place machine‐like functioning above human needs. In this paper, a mixed‐methods approach is used to investigate the relationship between bureaucracy and fairness in public administration. The research is based on an interview study with 60 employees for the generation of hypotheses and an online survey with 1632 participating employees of the German Federal Criminal Police Office. The qualitative results indicate that aspects of skill underutilisation, bureaucratic organisational structures, and silo mentality are potential predictors of fairness in the public administration context. The relationships of these predictors to fairness are validated using structural equation and mediation models. The results provide insights into the motivational needs of employees who perceive excessive bureaucratic regulations in their organisation. From this, well‐founded measures for improving fairness in public administration can be derived. Furthermore, two preliminary measures for measuring silo mentality and bureaucracy climate are introduced. Points for practitioners A workplace that is perceived as bureaucratic can have negative effects on employee perceptions of fairness. Bureaucracy is often criticised across the board, and it remains unclear which elements of it are perceived as disruptive. Bureaucracy is perceived as unfair, in particular when it hinders transparent and effective communication and personal career development. Unfair bureaucracy can be reduced by dismantling communicative silos and decentralising personnel management.